2018
DOI: 10.1007/s12035-018-0964-5
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic Diurnal Synthesis and Signaling of Retinoic Acid in the Rat Pineal Gland and Its Action to Rapidly Downregulate ERK Phosphorylation

Abstract: Vitamin A is important for the circadian timing system; deficiency disrupts daily rhythms in activity and clock gene expression, and reduces the nocturnal peak in melatonin in the pineal gland. However, it is currently unknown how these effects are mediated. Vitamin A primarily acts via the active metabolite, retinoic acid (RA), a transcriptional regulator with emerging non-genomic activities. We investigated whether RA is subject to diurnal variation in synthesis and signaling in the rat pineal gland. Its inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
0
9
0
1
Order By: Relevance
“…A huge number of epidemiological studies have reported the association between the nutritional status of dietary vitamins and cardiovascular disease (CVD); however, epidemiological research and randomized controlled trial (RCT) experiment results are inconsistent ( 6 8 ). Previous animal studies have demonstrated that dietary vitamins regulated the oscillation of circadian clock genes in the central nervous system and were involved in the synthesis of the circadian rhythm neurotransmitters ( 9 , 10 ). The disrupted clock genes and circadian rhythm neurotransmitters have been demonstrated to be related to the development of CVD ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…A huge number of epidemiological studies have reported the association between the nutritional status of dietary vitamins and cardiovascular disease (CVD); however, epidemiological research and randomized controlled trial (RCT) experiment results are inconsistent ( 6 8 ). Previous animal studies have demonstrated that dietary vitamins regulated the oscillation of circadian clock genes in the central nervous system and were involved in the synthesis of the circadian rhythm neurotransmitters ( 9 , 10 ). The disrupted clock genes and circadian rhythm neurotransmitters have been demonstrated to be related to the development of CVD ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that retinoic acid can modulate melatonin synthesis by affecting the activity of AANAT. 71 Moreover, PTN, which is functionally similar to MDK, may also regulate melatonin synthesis, given that the expression of MDK is responsive to retinoic acid. 72 Furthermore, our findings highlight the role of GPCRs in cell-cell interactions.…”
Section: Ligand-receptor Communication In Pineal Cells Influences Mel...mentioning
confidence: 99%
“…The Drosophila ROR homolog, ultraspiracle, has been studied for its endocrine function related to the hormone ecdysone [274,275], but it is known to be important for retinoid metabolism in eye development and tissue regeneration [276,277] both having functional conservation. Interestingly, retinoids are crucial for retinal development and appear linked to melatonin function [278]. However, functional relatedness and melatonin binding remain to be determined.…”
Section: Melatonin Life Extension In Drosophila Models Of Aging and Diseasementioning
confidence: 99%